THE KIPLING SOCIETY MINUTES OF THE 97TH ANNUAL GENERAL MEETING. - Bubb, Alex (Kipling Journal, 2025)
The article summarizes the 97th Annual General Meeting of the Kipling Society, highlighting ongoing activities, membership updates, and administrative developments. Topics include event programming and speaker highlights, changes in membership trends, and the transfer of the Society's library to Haileybury College for preservation.